Impact of different spacers on the conjugation between Anderson-Evans polyoxometalates and peptides - Yu, Haihong; Honisch, Claudia; Frigo, Mattia; Balice, Nicola; Tagliavini, Valeria; Zhao, Xue; Stramiglio, Elisabetta; Campofelice, Ambra; Serratì, Simona; Azzariti, Amalia; Porcelli, Letizia; Zanetti Polzi, Laura; et al. (Frontiers in Chemical Biology, 2024)
The Anderson-Evans polyoxometalates (POM) display a promising anticancer activity. The conjugation with the GRP-receptor antagonist peptide Demobesin (fQWAVGHL-NHEt) was exploited to impart cell targeting capabilities and improve the selectivity of such polyanions. However, the POM interacts with the grafted peptides, inducing chains folding and self-assembly of the resulting hybrids, thus decreasing their recognition ability. Within this context, a tailored spacer, including two domains, i.e., a hydrophilic one (1,13-diamino-4,7,10-trioxatridecan-succinamic acid, Ttds) and a tetra-anionic one (Glu-Glu-Glu-Glu-βAla, EEEE-βA) was previously utilized to mitigate such interaction. In this work, hybrid POMs containing only Ttds or EEEE-βA were prepared and the contribution of the two spacers was separately studied by using 2D NMR, fluorimetry and circular dichroism (CD). Transmission electron microscopy (TEM) was also used to observe the impact of the different spacers on self-assembly. Owing to the relevant effects observed for EEEE-βA, MD calculations were finally performed to elucidate its behavior when incorporated in the hybrid POM. Our results show that, despite the stronger impact of EEEE-βA spacer, only when both spacer are present together it is possible to observe a significant effect on the retention of peptide's secondary structure and recognition capability.